Observations of Cold Front Features at High Spatiotemporal Resolution Using the Atmospheric Imaging Radar - Mahre, William Andrew (My University, 2016)
Over the past 40+ years, cold front vertical structure has been studied for the purpose of increased understanding of convection initiation and aviation safety. Traditional scanning radars tend to not be well-suited for observing small-scale features due to low spatial resolution and slow volume coverage patterns (VCPs). While some previous studies have achieved high spatial or temporal resolution, this study is unique in that cold front vertical structure is observed at both high spatial and temporal resolution without any mechanical movement using the Atmospheric Imaging Radar (AIR). This mobile, X-band, phased array radar offers relatively high spatial (0.5 degree in elevation, 30 m in range) and temporal (300 ms) resolution while in range-height indicator (RHI) scanning mode. Because the AIR is an imaging radar, electromagnetic energy is transmitted in a wide fan beam pattern in elevation, allowing for use of digital beamforming to create simultaneous receive beams. This offers an additional advantage over traditional, pencil-beam radars: because all receive beams are simultaneous, differential vertical advection can be distinguished from temporal evolution. The ability of the AIR to obtain these simultaneous RHIs without any mechanical movement allows for unique analysis of cold front structure which would otherwise be difficult or impossible. Features such as Kelvin-Helmholtz Instabilities, low-level mass transport (referred to as feeder flow), transverse jet oscillations, and regions of heightened spectrum width will be analyzed and discussed in this study, which aims to improve understanding of small-scale, rapidly evolving features behind the leading edge of a cold front.
Keywords: Cold front; Phased array; High resolution; Imaging radar